The Image of the Black Sea in Train Names - Tomasik, Piotr (Poznańskie Studia Slawistyczne, 2024)
The article is devoted to the names of passenger trains referring to the Black Sea in Bulgaria, Romania, Turkey, the USSR, Ukraine, Georgia and Russia. The author presents an onomastic and cultural analysis of the collected names of passenger connections. The conclusion is that a significant number of excerpted names meet the requirements of the rhetorical category of loci amoenus, and many names of international train connections allow them to be included in the group of loci communes.